Optimal Reconfiguration of Thermoelectric Generation System Under Heterogeneous Temperature Difference - Zheng, You; Zhang, Enyou; An, Peng (Frontiers in Energy Research, 2022)
In view of the low efficiency of thermoelectric generation systems in different regions, this paper designs an optimization and reconfiguration of thermoelectric power generation system under heterogeneous temperature differences (HTD) based on particle swarm optimization (PSO) algorithm, so as to make full use of various thermal energy resources and obtain higher electrical output power, which realize multi-directional utilization of energy. In addition, PSO algorithm is a simple optimization strategy with a straightforward operation mechanism and fewer parameters to control during calculation. The research shows that when TEG array is in multiple HTD states, PSO algorithm has a stronger ability to get rid of local optimization, which can reduce power loss and improve energy conversion efficiency. On this basis, PSO algorithm is used to reconfigure the 15×15 symmetric TEG array. The experimental simulation analysis based on MATLAB platform is carried out to verify the feasibility of PSO algorithm.